Sistem Pendukung Keputusan Rekomendasi Pemilihan Mobil Bekas Dengan Menggunakan Metode Moora di UD.Timur Mobil - Angel Theresia Zari Pratama Dowa; Tri Ana Setyarini (Lembaga Pengembangan Kinerja Dosen, 2025)
Cars are one of the transportation facilities that is growing quite rapidly in Indonesia, along with the increasing number of people who need vehicles, namely cars because of comfort and safety. Prospective buyers or consumers face difficulties in selecting the right car that fits the desired criteria because prospective buyers are faced with many criteria. Therefore, a system or application is needed that can help customers make decisions about choosing a used car. This decision support system for selecting used car recommendations was created on a website basis to assist buyers or consumers in managing and obtaining information related to the decisionmaking system in selecting used cars. In this research, the application was built using the Moora method, which is one method that can be used to assist the decisionmaking process in a decision support system. This method produces ranking data on alternative types of used cars to determine the best alternative based on the ranking results. The final result expected from this research is to be able to provide solutions to consumers to determine the decision on a used car that suits the consumer's wishes with the criteria that have been determined.